THE RELATIONSHIP BETWEEN TEACHER SELF-DEVELOPMENT AND SUCCESS IN IMPROVING STUDENT ACHIEVEMENT IN THE ERA OF INDEPENDENT CURRICULUM IMPLEMENTATION:QUALITATIVE STUDIES - Imam Hanafi; Markus Oci; Fahrina Yustiasari Liriwati; Armizi; Yusak Noven Susanto (CV. ADIBA AISHA AMIRA, 2023)
In the context of Indonesia's independent curriculum implementation, this qualitative study investigated the connection between teacher self-improvement and student achievement success. Semi-organized interviews were directed with 50 Indonesian educators, and the information was analyzed using a topical examination. The discoveries recommend that instructor self-improvement influences the execution of the autonomous educational plan and understudy accomplishment. Time constraints, lack of resources, and motivation were identified as supporting or hindering teacher self-development. It was discovered that the leadership of a school plays a crucial role in encouraging teacher self-development. The study suggests that educators, school administrators, and educational policymakers should encourage and support teacher self-development to improve school teaching and learning. Both the effects of teacher self-development on other outcomes and the obstacles and facilitators to teacher self-development require additional research.